2017
DOI: 10.1142/s0218810417500010
|View full text |Cite
|
Sign up to set email alerts
|

Finger Trauma Due to Surfing; A Case Series and Analysis of Fracture Patterns

Abstract: From this case series we can conclude that surfing may lead to significant trauma to the fingers, mainly due to the leash. This can be caused by grasping the leash while it snaps to tension, which may lead to hyper flexion of the distal phalanx, resulting in a typical trans-phalangeal fracture. Also, when the leash is wrapped around a finger or grasped near the attachment of the leash to the board, ring avulsion-like trauma may occur, leading to open fractures or (partial) amputations. Recognizing that surf le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…13 Hand injuries, which are less frequent, most commonly consist of skin injuries, but surfers who decide to seek emergency care for their hand tend to present with fractures instead. 1,4,5 However, we found very little evidence pertaining to follow-up and long-term outcomes after fracture management. Follow-up is difficult because many patients are holidaymakers and go home after the initial treatment.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…13 Hand injuries, which are less frequent, most commonly consist of skin injuries, but surfers who decide to seek emergency care for their hand tend to present with fractures instead. 1,4,5 However, we found very little evidence pertaining to follow-up and long-term outcomes after fracture management. Follow-up is difficult because many patients are holidaymakers and go home after the initial treatment.…”
Section: Introductionmentioning
confidence: 84%
“…Follow-up is difficult because many patients are holidaymakers and go home after the initial treatment. 5 This case study presented a unique opportunity to assess long-term outcomes after an acute surfing hand injury. This case was reported based on CARE guidelines.…”
Section: Introductionmentioning
confidence: 99%
“…Parts of the board, such as the sharp fins or the tail, are mainly responsible. 7 , 29 Development of new fin and board designs may help prevent these injuries. In surfing, a too strong surf and therefore contact with the sea ground or collision with the board are also responsible for this type of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Surfing activities are a popular sport on the Gold Coast with both locals and tourists, and with 57 km of coastline, 1 the Gold Coast is also home to many regional and international surfing competitions. Surfing injuries have previously been studied in coastal Australian areas 2 including Byron Bay 3 and Sydney, 4,5 and globally in other areas such as Hawai’i, 6 the United Kingdom, 79 France 10 and the United States of America. 11 Dimmick et al .…”
Section: Introductionmentioning
confidence: 99%
“…report surfing-related injuries to range from 2.2 to 3.5 injuries per 1000 hours of surfing in recreational surfers, and 6.6 injuries per 1000 hours in competitive surfers. 5 Studies on surfing-related injuries have reported varying rates of a range of injuries including bruising and lacerations, facial bone fractures, globe rupture, cervical spine fractures and dislocations, 4,5,9 finger trauma, 10 joint sprains, muscle or tendon tears and ruptures, upper and lower limb fractures, and anterior shoulder dislocations. 7,8 Richards et al .…”
Section: Introductionmentioning
confidence: 99%